2015
DOI: 10.1007/s13753-015-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Understanding the Reduced Spring Dust Storm Frequency in Inner Mongolia, China

Abstract: Spatiotemporal patterns of dust storms are affected by climate change through changes in convective instability, regional meteorological characteristics, and local sediment supply. Linking dust storm dynamics to climate change helps the understanding of what controls the initiation of dust storms, and assists the prediction of future dust storm occurrence. This study examines the temporal dynamics of spring dust storms in Inner Mongolia, a major dust source area in East Asia. We found that severe spring dust s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The number of meteorological observation sites with severe dust storm records has declined from over 200 in the 1950s to ~75 in the 2000s at a rate of 3.20 sites per year (Figure b). This significantly declining trend in dust storm activity agrees with previous findings in China (e.g., Ding et al, ; Fan et al, ; Qian et al, ; Zhu et al, ), which is related to the changes in the large‐scale atmospheric circulation patterns, the local to regional climate conditions, and the soil and vegetation conditions at the ground surface (Li et al, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The number of meteorological observation sites with severe dust storm records has declined from over 200 in the 1950s to ~75 in the 2000s at a rate of 3.20 sites per year (Figure b). This significantly declining trend in dust storm activity agrees with previous findings in China (e.g., Ding et al, ; Fan et al, ; Qian et al, ; Zhu et al, ), which is related to the changes in the large‐scale atmospheric circulation patterns, the local to regional climate conditions, and the soil and vegetation conditions at the ground surface (Li et al, ).…”
Section: Resultssupporting
confidence: 90%
“…At this point, it is beyond the scope of the current study to pinpoint a possible physical hypothesis for the intensified clustering of severe dust storm activity in China. It is likely that various factors, such as large‐scale atmospheric circulation, regional wind intensity and rainfall pattern, and vegetation coverage change induced by warming and human activity, are involved (Ding et al, ; Fan et al, ; Li et al, ; Qian et al, ; Shao & Dong, ; Tan & Li, ; Zhou & Zhang, ). Future weather composite studies can identify favorable synoptic systems that correspond to the days with more severe dust storm records.…”
Section: Discussionmentioning
confidence: 99%
“…Asia dust storms gradually decline since 1970s according to the record from China over the desert area 2 . Although some studies 35 , 36 suggested that the earlier vegetation green-up may have reduced the dust storm frequency, the research community has no solid conclusion of the determining factor(s) of dust climatology. And the large scale drought over Asia resulted in severe dust storms in 2010 37 , indicating the extreme dust storm events could still occur in the presence of favorable meteorology condition.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 2000s, judging from the increasing frequency of such episodes in not only the source region (Inner Mongolia and northeastern China) but also in downwind regions, including Korea and Japan (Kurosaki and Mikami 2003;Tian et al 2007;Kim 2008;Lee and Sohn 2011), this situation appeared to be worsening. However, in recent years, it is reported that the frequency of dust storms in China is decreasing (Li et al 2015). These previous studies clearly show the large interannual variability of dust occurrence in the East Asian region (Hsu et al 2012).…”
Section: Introductionmentioning
confidence: 85%